A NEW LEVEL OF DEVELOPMENT OF LEGAL EDUCATION AND SCIENCE IN UZBEKISTAN - Murtazaev Dilshod (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This scientific article analyzes the trend of innovative approaches to legal education and science in Uzbekistan in recent years. The significance of the latest decisions and decrees of the president and the government in reforming higher education and professional legal education is revealed. In addition, the role of the community and volunteer groups in a democratic society and legal education is emphasized